2019
DOI: 10.3389/fphar.2019.01464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eurycoma longifolia Stem Extract on Uric Acid Excretion in Hyperuricemia Mice

Abstract: Background: Eurycoma longifolia is a tropical medicinal plant belonging to Simaroubaceae distributed in South East Asia. The stems are traditionally used for the treatment of sexual insufficiency, fever, hypertension, and malaria. Furthermore, it has antidiabetic and anticancer activities. Recently, it has been reported to reduce uric acid, but the mechanism is unclear. Hypothesis/Purpose: The aim of this study is to explore the effect and mechanism of E. longifolia stem 70% ethanol extract (EL) and its active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…Although ALP belonging to XO inhibitors has been mainly used to treat Evidence-Based Complementary and Alternative Medicine hyperuricemia, this drug has been associated with severe cutaneous adverse reactions [33]. erefore, many previous studies have been conducted to develop safe therapeutic agents using natural products for hyperuricemia without side effects [14,19,30]. is study showed the antioxidant, XOD-inhibitory, and antihyperuricemic activities of DMLEs and determined active components.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although ALP belonging to XO inhibitors has been mainly used to treat Evidence-Based Complementary and Alternative Medicine hyperuricemia, this drug has been associated with severe cutaneous adverse reactions [33]. erefore, many previous studies have been conducted to develop safe therapeutic agents using natural products for hyperuricemia without side effects [14,19,30]. is study showed the antioxidant, XOD-inhibitory, and antihyperuricemic activities of DMLEs and determined active components.…”
Section: Discussionmentioning
confidence: 93%
“…erefore, more effective therapeutic agents for hyperuricemia with no adverse effects are needed. In previous studies, new therapeutic methods using herbs were offered to overcome these limitations of drugs for hyperuricemia [19].…”
Section: Introductionmentioning
confidence: 99%
“…The method of protein samples preparation was reported in literature [ 29 ]. SDS-polyacrylamide gel (SDS-PAGE) electrophoresis was used to isolate protein and then transferred to PVDF membrane (Merck Millipore, Bedford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…According to the literature, potassium oxonate (PO) (an uricase inhibitor) with or without high purine food is usually used as hyperuricemia inducer in rats/mice, but the experimental protocols are different. For example, the duration of modeling was 7 [ 26 ] or 14 days [ 27 ], PO was orally [ 28 ] or intraperitoneally injected [ 26 ], PO dose was 200 [ 29 ], 250 [ 30 ] or 300 mg/kg [ 31 ], etc. The administration time is not uniform, resulting in a large difference between the data by different research groups, with some opposite results.…”
Section: Introductionmentioning
confidence: 99%
“…Quassinoids in E. longifolia hadhuman urate transporter 1 (URAT1) inhibition activity by reducing blood uric acid levels in induced hyperuricemia animal model (Bao et al, 2019). Study by Liu et al (2019) presented that E. longifolia reduced ankle swelling caused by gout in low and medium doses which indicated that E. longifolia has anti-gout effect.…”
Section: Antigoutmentioning
confidence: 97%